Frequency support strategy for single-Stage grid-Connected photovoltaic generation with active power reserves - Fu, Xuan; Wang, Xueying; Jia, Qi; Wang, Hongjiang (Frontiers in Energy Research, 2022)
Large-scale photovoltaic (PV) generation grid connection causes lack of inertia and insufficient frequency regulation capacity of power system. To solve this problem, this study proposed the active power-frequency droop control (APFDC) and virtual inertia control (VIC) for single-stage PV generation. PV generation is able to participate in the grid frequency regulation by improving the control system of voltage source converter (VSC). The effect of control parameters on the inertia characteristic of PV generation is analyzed. On this basis, the distribution mechanism of unbalanced active power among PV generators with inertia control strategy is revealed. The simulation results indicated that PV generation can be controlled by setting the control strategy of the voltage source converter (VSC) to reduce or increase the active power; it also takes part in the frequency regulation of the system. The inertia provided by PV generation is controllable and frequency-dependent, increases with the increase in control gain, the decrease in the time constant of VIC, and the decrease in phase-locked loop (PLL) control bandwidth.